Under Nutrition in Less than Six Months Needs More Attention - Muthukumar , Aarthi; Menon, Pramila; Mane, Shailaja; Giri, Purushottam A (Indian Journal of Community Health, 2024)
Under nutrition in infants is a critical public health concern with far-reaching consequences on child growth and development, particularly during the crucial first six months of life(1). This formative period lays the foundation for future health outcomes and any disruption in adequate nutrition can lead to a host of long-term issues, including stunted growth, compromised immune function, and impaired cognitive development(2). According to the Black et al. (2008) study, these factors are responsible for approximately 2.2 million deaths annually and contribute to 21% of disability-adjusted life-years in this age group(3). The 2011 United Nation Children's Fund (UNICEF) Global Nutrition report indicated that more than 311 million children (32% of all children) were undernourished. Globally, more than four million children died within a year of their birth due to inadequate nutrition.In addition, poor infant nutrition has been shown to be responsible for more than 40% of deaths in children younger than 5 years, particularly during their first month of life(4). The adverse effects of infant undernutrition include physical disabilities, poor school attendance, diabetes, hypertension and cardiovascular disease which may affect the subsequent generation(5).Therefore, undernutrition may have negative long-term consequences for a country’s economic growth and development. The impact of undernutrition on child growth and development starts in utero. Maternal undernutrition has been associated with poor foetal growth which may result in low birth weight (LBW, weight at birth less than 2500 g), small for gestational age (SGA, newborns weighing less than the 10th percentile of a sex-specific reference population) and preterm birth (PTB, children born before 37 gestational weeks(6). In 2016, UNICEF reported that 15% (20 million) of newborns worldwide had LBW and 10% (15 million) PTB. In 2010, 32.4 million newborns worldwide were SGA. The prevalence of SGA was 27% in LMICs, with SSA having one of the highest prevalence(7). The first six months of life are characterized by rapid growth and development, as well as a heightened vulnerability to nutrition-related risks(8).